DECORATED YALINAYAK MOSQUE FOUNTAIN IN TIRE - Hür Kamil BİÇİCİ (Fırat University, 2021)
Fountain, barefoot in the north east portion of the last congregation of the mosque is situated in a courtyard. Marble section of fountain is